IDEOLOGY CRITIQUE OF ACEHNESE WOMEN'S POLITICAL PARTICIPATION: A COMMUNICATION TRADITION ANALYSIS USING FRANKFURT CRITICAL THEORY AND ASMA BARLAS FEMINISM - Chairozi, Fachri (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2025)
This research uses a descriptive qualitative method through a library receach to analyse relevant sources based on the critical theory of the Franfrut school to see the phenomenon of distorted communication in society due to the power structure. This research also refers to Asma Barlas' views on gender equality in the Qur'an. The aim is to find out the level of women's participation in politics that is hindered by excessive sacredness in culture and spirituality. The results of the research show that women's political interests in Aceh are distorted by the encouragement of traditional knowledge formed on cultural and spiritual arguments, as evidenced by the fatwa issued to limit women's political expression in the context of leadership in Aceh. For this reason, this research offers ideas or breakthroughs to realise the interests of 30 per cent women's representation through general elections.